The role of veterinarians in the recognition of animal cruelty: lessons from a pilot study in the Netherlands - Wijk, Anton Ph. van (Animal abuse and interpersonal violence, 2024)
Detecting animal cruelty is challenge, even for the veterinarians. For this reason, the Forensic Veterinary Expert Centre was established in the Netherlands. Veterinarians who suspect incidents of animal cruelty can seek help from the forensic experts to assess the cases. In this chapter, we describe the working method of this center and the results from a pilot study 46 cases are discussed. Out of the total, 19 cases are suspected to involve incidents of animal cruelty. In these cases, the veterinarians received a report of suspected animal cruelty within 48 hours to assess if any follow-up actions can be pursued. Given their expertise, the role of veterinarians has becoming more important in cases of animal cruelty.